Managing Risk on A Pharmacy Enterprise Supply Chain Using House of Risk Approach - Nafi’ah, Aenun; Mahbubah, Nina (Journal Knowledge Industrial Engineering (JKIE), 2021)
Pharmacy CBA is a trading business that engages in pharmaceutical and medical devices. Uncertainty and complexity have been identified as risks in business supply chains. Further measurement is needed in order to enhance the effectiveness of the pharmacy business process. The purpose of this study is to identify risk events and risk agents, calculate the risk value in the supply chain flow from upstream to downstream, and determine efforts to minimize risk. The method used in this research is HOR 2 phases, through a SCOR-based approach. The study begins with the identification of risk events and risk agents based on SCOR, then calculates the level of severity, occurrence, and correlation for the calculation of the HOR 1. Identified 45 risk events, 23 risk agents, and 19 actions to minimize risk. Aggregate risk potential is calculated as a result of HOR 1. From 23 risk agents, ten are prioritized based on the most significant ARP value. In the calculation of HOR 2, 10 risk mitigation strategies are obtained to minimize risk along with the supply chain stream. There are four approaches to implementing the ten mitigations: HR Development, Customer Relationship Management-based approach, Supplier relationship management, and facility design.